1995
DOI: 10.1063/1.469684
|View full text |Cite
|
Sign up to set email alerts
|

Competition between energy and phase relaxation in electronic curve crossing processes

Abstract: We present results from simulations of vibrational energy and phase relaxation and electronic curve crossing using a multilevel formulation of Redfield theory, which demonstrate the shortcomings of the optical Bloch approximation and the importance of coherence transfer processes in the relaxation dynamics of multilevel systems. Specifically, we show that for a harmonic well, energy relaxation can occur with retention of vibrational phase, and that for sufficiently strong electronic coupling, the product of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 31 publications
5
117
0
Order By: Relevance
“…It is difficult to believe that the phase of wavepacket motion gets little distortion with passing through several internal conversion processes and losing large energy of 1.55 eV. However, recently there are some papers which support such phenomenon theoretically [26].…”
Section: Resultsmentioning
confidence: 92%
“…It is difficult to believe that the phase of wavepacket motion gets little distortion with passing through several internal conversion processes and losing large energy of 1.55 eV. However, recently there are some papers which support such phenomenon theoretically [26].…”
Section: Resultsmentioning
confidence: 92%
“…Surprisingly, this lifetime is much greater than the 100-200 fs time constant for energy transfer from B* or H* to P (van Brederode and van Grondelle 1999). The long-lived coherence was theoretically predicted by Jean and Fleming (1995) using the multilevel Redfield theory. It was shown that, for a harmonic well, the vibrational phase can be retained during energy relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Density-matrix formalism permits us to take into account the finite time of vibrational relaxations and dephasing (Redfield 1965). On the basis of the Redfield theory, a theoretical study of coherent electron transfer was performed by the approach of a single nuclear mode coupled to two electronic states (Jean and Fleming 1995;Jean et al 1992;Jean 1994). The oscillatory dynamics in the P*-stimulated emission band were theoretically studied by an approach of one electronic transition coupled to one or two vibrational modes Leegwater 1995;Lin et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The harmonicity guarantees frequency matching between the vibronic levels, resulting in very efficient coherence transfer between vibronic levels. 26 The cage-like structure of the molecule protects the oscillator from the stochastically fluctuating solvent, also reducing pure dephasing. This behavior shows close resemblance to the vibrational relaxation of dihalogens in rare gas matrices.…”
Section: Vibrational Population Relaxation In the Singletmentioning
confidence: 99%